Implementing and sustaining Point of Care ROTEM® into a trauma activation protocol for the management of patients with traumatic injury: A mixed-methods study. Issue 3 (May 2023) - Wake, Elizabeth; Walters, Kerin; Winearls, James; Marshall, Andrea P.
Abstract: Background: Up to 40% of patients with traumatic injury experience critical bleeding, many requiring transfusion of blood products. International transfusion guidelines recommend the use of viscoelastic testing to guide blood product replacement. We implemented a Point of Care ROTEM® blood test for trauma patients who present and initiate a trauma activation. Objectives: The aim of this study was to undertake an evaluation of the implementation data to identify factors which helped and hindered this new practice. Methods: A sequential mixed-methods design was conducted to evaluate intervention implementation. The intervention was designed with interprofessional collaboration and incorporated education and skills training supplemented with a decision aide. Patients aged ≥ 18 years who met the trauma activation criteria were included. Data collection occurred throughout the 21-month implementation period inclusive of initial roll out, maintenance and sustainability and include the number of ROTEM® blood tests taken and clinical characteristics of patients. Individual interviews were conducted with health professionals with experience of the intervention after the implementation period was complete. Results: A total of 1570 eligible patients were included. The number of patients who had a ROTEM® blood test taken increased over time to 63%. The proportion of patients having a ROTEM® blood test obtained was higher for major trauma patients (n=162, 66.9%) who were admitted to the Intensive Care Unit. Regression analysis found trauma service presence on arrival and the sustainability phase of implementation increased the likelihood of having a ROTEM® taken. Qualitative data suggest that a more tailored approach to intervention implementation would assist with adoption. Conclusion: Implementation of new practice requires careful planning and should be undertaken with input from end-users. Continuous evaluation is necessary to support ongoing implementation and sustainability. To ensure effective implementation occurs, complex interventions need to be made workable and integrated in everyday health care practice.